Tingkat Pemahaman Anggota Kelompok Pengajian Surau Al Mu’min Jl. Waspada Tembilahan Terhadap Hukum Waris Islam - Tia Juliana; Dina Gustina; Haikal Rizky Adhinata; M. Jibrian; Herdiansyah; M. Fajri Gunawan (Indragiri Law Review, 2025)
Allah SWT created the world along with other entities. One of them is mankind, humans are creations specially bestowed by God. Humans will live their lives until Allah calls them back. Every life in this world will inevitably end in death. The death of a human being will result in the transfer of property rights of the deceased (the mayit) to their surviving heirs. The transfer of property rights includes both animate and inanimate assets. This process is commonly referred to as inheritance.Inheritance is something we often hear about upon someone's passing. Inheritance is the property left behind by the deceased to their surviving heirs who will inherit the residual assets (the inheritance). Every family has its own way of dividing the inheritance; usually, they divide it based on the method of Islamic inheritance law, customary law, familial consensus, or Indonesian civil law. Public understanding certainly varies, which is why this article was created: to examine the extent of the community's understanding of Islamic inheritance law and whether they have also practiced Islamic inheritance law in the division of inheritance.The data was collected through questionnaires filled out at a weekly recitation group (pengajian) at the Al-Mu'min prayer house (surau) on Jalan Waspada Tembilahan, comprising 80 members. The weekly recitation is usually attended by congregations from various social strata, including housewives, workers, and the elderly.This research aims to determine the extent of the understanding among the mothers in the recitation group regarding the division of inheritance according to Islamic inheritance law (Fara'id) and whether they have implemented the Islamic inheritance law in their actual inheritance division. This study uses an empirical legal approach with a qualitative method based on primary data obtained through surveys with the mother members of the recitation group at Surau Al-Mu'min.The research findings indicate that most members of the weekly recitation group at Surau Al-Mu'min still do not understand Islamic inheritance law and use a system of equal distribution of the inheritance assets. In many cases, the resulting decision tends toward an equal division or through a system of voluntary grant (hibah) or surrender of rights, which often deviates from the fixed portions stipulated in the Fara'id provisions. Nevertheless, they adopt the system of equal distribution because it is considered easier and avoids conflicts.This study concludes that most of the mothers who are members of the weekly recitation group at Surau Al-Mu'min do not yet understand and have not yet implemented Islamic inheritance law in the division of inheritance within their families.